Peran Guru Pendidikan Agama Katolik di Slb-A Karya Murni Medan - Xaverius Felix; Jonathan Aley; Jessica Helsa (Journal New Light, 2023)
Opening a Catholic Religious Education (PAK) class for blind children is not an easy thing. Teachers have the capacity and ability to handle children with special needs such as the blind. The research entitled The Role of Catholic Religious Education Teachers at Karya Murni Special School (SLB-A) Medan was carried out with the aim of understanding the role of Catholic religious education teachers at Karya Murni Special School (SLB). Medan. by providing Catholic religious education to blind students. In this research the author used qualitative descriptive analysis techniques combined with interview methods with school participation, specifically: Principal, two Catholic religious education teachers, two Catholic religious education teachers and six blind students.